2004
DOI: 10.2527/2004.8261818x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of imbalance between energy and nitrogen supplies on microbial protein synthesis and nitrogen metabolism in growing double-muscled Belgian Blue bulls1

Abstract: Six double-muscled Belgian Blue bulls (initial weight: 345 ± 16 kg) with cannulas in the rumen and proximal duodenum were used in two juxtaposed 3 × 3 Latin squares to study the effect of a lack of synchronization between energy and N in the rumen on microbial protein synthesis and N metabolism by giving the same diet according to three different feeding patterns. The feed ingredients of the diet were separated into two groups supplying the same amount of fermentable OM (FOM), but characterized by different le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
10
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 29 publications
3
10
1
1
Order By: Relevance
“…This occurrence was supported by the fact that the main energy contribution of the forages originates from carbohydrate fraction B 2 (Malafaia et al, 1998;1999). This condition will provide the necessary synchronism between nitrogen and energy (from carbohydrates) for microbial protein synthesis (Vieira et al, 2000c;Valkeners et al, 2004;Yang et al, 2010), a situation similar to that found in the present study. The specific growth rate was not influenced by the treatments.…”
Section: Discussionsupporting
confidence: 87%
“…This occurrence was supported by the fact that the main energy contribution of the forages originates from carbohydrate fraction B 2 (Malafaia et al, 1998;1999). This condition will provide the necessary synchronism between nitrogen and energy (from carbohydrates) for microbial protein synthesis (Vieira et al, 2000c;Valkeners et al, 2004;Yang et al, 2010), a situation similar to that found in the present study. The specific growth rate was not influenced by the treatments.…”
Section: Discussionsupporting
confidence: 87%
“…In the current experiment, there was no significant effect on the microbial protein synthesis when a 12-h imbalance of a daily OEB variation of 20 or 40 g of OEB/kg of DM was created. This lack of response to an increased level of imbalance between energy and N supplies for the ruminal microbes is in agreement with results obtained in a previous study (Valkeners et al, 2004), which demonstrated that a lack of imbalance in the diet between the energy and N supplies for ruminal microbes was not detrimental to their growth as long as nutrient supply was balanced on a 48-h basis and the level of imbalance did not exceed 30 g of OEB/kg of DM.…”
supporting
confidence: 92%
“…The total tract and ruminal digestibility of OM and NDF measured with L0 were consistent with those generally measured on double-muscled Belgian Blue bulls (Fiems et al, 1997;Valkeners et al, 2004). The theoretical ruminal N degradability (in sacco values), estimated from the Dutch tabular values (CVB, 2000) averaged 50.2 and 72.4%, respectively, for LRDN and HRDN.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…The consumption of protein and higher energy will generate faster growth rate (Soeparno 2005). Degradation of carbohydrate and N supply in the rumen of cattle affected the efficient use of energy and protein and the growth rate (Valkeners et al 2004). Changes source of carbohydrates and protein in the feed are influenced by specific changing substrates such as starch and protein NDF with the NPN important effect on the balance (Cabrita et al 2006).…”
Section: Performancementioning
confidence: 99%